The Organizational Structure of the "Toronto Native Times" (1968-1981) - Riggins, Stephen Harold (Anthropologica, 2022)
This article describes the history of a native Canadian newspaper published in Toronto between 1968 and 1981 and appropriately titled the Toronto Native Times. An attempt is made to show how the operating environments of native periodicals generally hamper fulfillment of their optimal roles. As such, the article provides information which is potentially useful to policy makers. While its opening sections are purely descriptive, the latter sections of the article relate the organizational structure of the Toronto Native Times to that of other native publications in order to provide a general perspective on problems confronting the native Canadian press.